2008
DOI: 10.1017/s0033291708004261
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of temperament endophenotype candidates for early emergence of the core cognitive component of eating disorders

Abstract: Background. This study was designed to investigate potential temperament endophenotypes for clinically significant importance of shape and weight.Method. Seven temperament risk factors for eating disorders and the Eating Disorder Examination were assessed in 699 female twins aged 12-15 years. Each variable was evaluated against the following endophenotype criteria : associated with illness in the general population ; found in non-affected family members at a higher rate than in the general population ; and, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…The three waves of data from the current study are from female twin adolescents as shown in Figure 1, where the participants and methodology of ascertainment for this sample have been previously described (Wade, Byrne, & Bryant-Waugh, 2008;Wilksch & Wade, 2010;Wilksch & Wade, 2009a).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three waves of data from the current study are from female twin adolescents as shown in Figure 1, where the participants and methodology of ascertainment for this sample have been previously described (Wade, Byrne, & Bryant-Waugh, 2008;Wilksch & Wade, 2010;Wilksch & Wade, 2009a).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The EDE was modified slightly for use with a younger population as described in detail previously (Wade et al, 2008;Wilksch & Wade, 2010;Wilksch & Wade, 2009a), and included questions that form four sub-scales: dietary restraint, and eating, shape and weight concern over the last 28 days.…”
Section: Weight and Shape Concernmentioning
confidence: 99%
“…Longitudinal study Eating disorders The most significant time of risk for the development of high levels of weight and shape concern was 13-15 years of age (Wade et al, 2008;Wilksch & Wade, 2009. Oral health/dentistry Environmental and epigenetics factors likely play a role in the timing of tooth emergence and bacterial colonization (Bockmann et al, 2011).…”
Section: Smoking and Bone Densitymentioning
confidence: 99%
“…These clinical markers should include, as far as possible, heritable traits (endophenotypes) and other biological parameters. So far, efforts to isolate specific biological markers of eating disorders have only partially succeeded [2][3][4][5][6][7] and usually they have been linked to specific clinical profiles [2,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%